Terp taikamosios kalbotėros barų - Hilbig, Inga; Jakaitė-Bulbukienė, Kristina; Žurauskaitė, Eglė; Daraškienė, Inga (Vilnius University Open Series, 2023)
This collection of articles in applied linguistics is dedicated to Prof. Meilutė Ramonienė‘s anniversary. The book is compiled of papers written by her students, colleagues, and friends from Lithuania, Latvia, Estonia, and Switzerland. These texts are from various fields and subfields of applied linguistics, i.e., family language policy, national language policy, linguistic attitudes, motivation to learn a second language, linguadidactics, text linguistics, and linguistic impoliteness. In the preface, a short overview of Prof. M. Ramonienė‘s academic path and her as personality is given, and there is one more non-academic text that presents and highlights her long lasting fruitful contribution to the networking of the Baltic scholars.